Kritik efter postkolonialiteten - Scott, David (K&K - Kultur og Klasse, 2024)
How can we best forge a theoretical practice that directly addresses the struggles of once-colonized countries, many of which face the collapse of both state and society in today’s era of economic reform? David Scott argues that recent cultural theories aimed at “deconstructing” Western representations of the non-West have been successful to a point, but that changing realities in these countries require a new approach. In Refashioning Futures, he proposes a strategic practice of criticism that brings the political more clearly into view in areas of the world where the very coherence of a secular-modern project can no longer be taken for granted.